2014
DOI: 10.1093/ckj/sfu046
|View full text |Cite
|
Sign up to set email alerts
|

Fasting during the month of Ramadan among patients with chronic kidney disease: renal and cardiovascular outcomes

Abstract: BackgroundFasting during the month of Ramadan is a religious obligation for Muslims who represent 20% of the world population. This study explores the safety of fasting for a whole month among patients with chronic kidney disease (CKD) with the possible risk of dehydration and hyperviscosity leading to deterioration of kidney functions and vascular thrombosis.MethodsWe followed CKD patients with stable kidney function who chose to fast during the month of Ramadan. A group of nonfasting CKD patients served as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 14 publications
0
47
0
Order By: Relevance
“…Their results suggested that dehydration occurs during daytime fasting and is reversed at sunset but that its effects are difficult to assess because of these daily fluctuations. Despite variations in kidney function, they did not notice any changes in blood pressure, which, however, does not necessarily exclude the possibility of dehydration [127]. Further studies should explore the possible impact of fasting and dehydration on cognitive functioning in greater depth and detail.…”
Section: Effects Of Dehydrationmentioning
confidence: 79%
See 1 more Smart Citation
“…Their results suggested that dehydration occurs during daytime fasting and is reversed at sunset but that its effects are difficult to assess because of these daily fluctuations. Despite variations in kidney function, they did not notice any changes in blood pressure, which, however, does not necessarily exclude the possibility of dehydration [127]. Further studies should explore the possible impact of fasting and dehydration on cognitive functioning in greater depth and detail.…”
Section: Effects Of Dehydrationmentioning
confidence: 79%
“…However, few studies have reported on the effect of dehydration due to IF without fluid consumption. One such study by NasrAllah and Osman [127] explored the effect of fasting among 52 patients with chronic kidney disease during RIF. Their results suggested that dehydration occurs during daytime fasting and is reversed at sunset but that its effects are difficult to assess because of these daily fluctuations.…”
Section: Effects Of Dehydrationmentioning
confidence: 99%
“…Such alterations have the potential to induce cardiovascular events. 7,31,32 However, several studies assessing the incidence of various cardiovascular outcomes failed to demonstrate increased risk during Ramadan. 9,20,33 Similarly, previous studies have failed to demonstrate increased stroke risk during Ramadan, comparing stroke admissions during the Ramadan to the previous month or to other months.…”
Section: Discussionmentioning
confidence: 99%
“…Several physiological changes such as changes in circadian rhythm,4 serum lipid and glucose levels5 as well as renal function markers and hematocrit levels,6 have been reported among observant Muslims during Ramadan. In addition, Ramadan has been associated with exacerbation of several medical conditions such as diabetes mellitus, migraines, and chronic kidney disease 7. Nevertheless, the effect of Ramadan on cardiovascular morbidity is not clear 8, 9…”
mentioning
confidence: 99%
See 1 more Smart Citation